2022
DOI: 10.2147/jpr.s379699
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Mapping of Acupuncture for Fibromyalgia from 1990 to 2022: A Bibliometric Analysis

Abstract: Background Fibromyalgia is a rheumatic disease with no specific laboratory markers and is insensitive to hormonal drugs and nonsteroidal anti-inflammatory drugs commonly used to treat rheumatism. Guidelines recommend that non-pharmacological therapy should be the first-line treatment for fibromyalgia. Since the publication of the first diagnostic criteria for fibromyalgia in 1990, studies on acupuncture for fibromyalgia have been reported periodically. This study aims to explore the intellectual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 66 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…When the values of Q and S are greater than 0.3 and 0.5, respectively, it ensures the credibility of the clustering structure and the reliability of the findings. 17 Else, keyword co-occurrence analysis and the detection of keyword burst intensity also contribute to the unveiling of research hotspots and anticipated future trends in this field.…”
Section: Methodsmentioning
confidence: 99%
“…When the values of Q and S are greater than 0.3 and 0.5, respectively, it ensures the credibility of the clustering structure and the reliability of the findings. 17 Else, keyword co-occurrence analysis and the detection of keyword burst intensity also contribute to the unveiling of research hotspots and anticipated future trends in this field.…”
Section: Methodsmentioning
confidence: 99%
“…It ultimately proved the efficacy of the EV71 vaccine in preventing HFMD or herpangina associated with EV71 in infants and young children, providing important reference value for EV71 prevention and gaining widespread attention in subsequent research. [ 18 ] In Figure 7 , the blue line represents the time interval and the red line represents the burst duration. The first cited explosion occurred in 2013 and originated from an article published in 2010.…”
Section: Resultsmentioning
confidence: 99%
“…Although other bibliometric studies related to FM exist, they did not comply with traditional bibliometric laws, and they used different methodologies compared with this study. Moreover, the covered topics were different, including FM and biomechanics, FM research, juvenile primary FM syndrome, acupuncture, and the top 100 Cited Articles on Fibromyalgia Syndrome [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific bibliography, FM and PA research can be found, including crosssectional studies [36,37], randomized controlled trials [38,39], systematic reviews and metaanalyses [11,40,41], and scoping reviews [23,42]. However, although other bibliometric analyses on FM exist [43][44][45][46][47], no bibliometric studies related to FM, pain, and PA have been found. The mapping of an area of scientific knowledge through a bibliometric analysis is useful to provide essential information to researchers, such as identifying research opportunities, trends in scientific production, and substantiating scientific research, among other utilities [48].…”
Section: Introductionmentioning
confidence: 99%